Books of Becoming: Memory Writing and Memory Sharing on 20th-Century Oshwal Jain Migration - Tine Vekemans (Religions)
This article examines the narrative of migration that circulates among Oshwal Jains today. It does so by closely analyzing a varied corpus of memory-writing, including autobiographies, family histories, community histories, memoirs, and social media discussing the settlement of Oshwal Jains from British India in East Africa between 1890 and 1950, and their subsequent onward migration from the late 1960s to the early 1980s. This article first presents a brief historical overview of South Asians in East Africa, and pieces together a picture of how and where Oshwal and non-Oshwal Jains featured within this colonial history. Operationalizing concepts from the field of memory studies, it then discusses which stories and memories are shared, and shows how they combine to form and sustain a community-affirming rags-to-riches narrative. Although the materials in the corpus can certainly help fill in some of the under-researched aspects of South Asian cultural history in East Africa, the narrative(s) of migration they present, with their telling tropes and silences, are indicative of dynamics and developments within the contemporary Oshwal Jain community. Therefore, by way of conclusion, the article interrogates the timing and intergenerational dynamics of the recent surge in memory sharing and memory writing by Oshwals settled around the globe.